“Could You, Perhaps, Pretty Please?”: Request Directness in Cross-Cultural Speech Act Realization - Heather Tatton (Studies in Applied Linguistics & TESOL, 2008)
I am grateful to Professor Beebe for introducing me to the field of discourse analysis. Since that first introductory class, I have continued to be intrigued by the many facets of discourse studies. I was so affected that in subsequent courses, if the option was available, I chose to focus my assigned research on an area related to discourse, including studies in pragmatics and conversation analysis. In addition, I have internalized much of what I learned from Professor Beebe and have a tendency to apply it to everyday conversations (sometimes to the dismay of my friends and family members). The article below is an excerpt from the first paper that I submitted to Professor Beebe. I remember it fondly and will always be thankful for her assistance and influence.